101 tales the great punchatantra collection (Noida : Wonder House, 2022)
This compilation of 101 tales from the Panchatantra aims to guide the young readers about wise conduct, human nature, and the right path for attaining success in life. Accompanied with beautiful illustrations and great morals, this book will inspire the child to follow the path of righteousness and abide by the wise rules of the world.